2016
DOI: 10.15562/jdmfs.v1i3.313
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction against the quality of dental health services at dental polyclinic of Tenriawaru General Hospital in Bone Regency

Abstract: Objective: Patient satisfaction against the quality of dental health serviceswas a comparison between the perception of care received by expectation before getting treatment. The Research was conducted at Tenriawaru General Hospital in Bone Regency based on the five dimensions of service quality, they were the assurance, empathy, responsiveness, physical appearance and medical services by using Likert scale. Material and Methods:The study was descriptive with a sample of 65 people. The research subjects were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 1 publication
2
18
0
1
Order By: Relevance
“…This suggests that male visit more dental and oral care providers. This survey is accordance with previous research, which states that respondents have higher satisfaction level in males (70%) [17]. However, this study is not accordance with research conducted in Jakarta [18] that demonstrated the employees and public society in Indonesia more dominates women.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This suggests that male visit more dental and oral care providers. This survey is accordance with previous research, which states that respondents have higher satisfaction level in males (70%) [17]. However, this study is not accordance with research conducted in Jakarta [18] that demonstrated the employees and public society in Indonesia more dominates women.…”
Section: Resultssupporting
confidence: 80%
“…In addition, another research showed that women visit more providers of dental and oral health services because more attention to the aesthetic and clean teeth and mouth. Women pay more attention to their appearance, while men do not heed it other than that women are more sensitive to emotion and empathy while men are more likely to care about better physical environment and faster and more flexible responses than women [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Women pay more attention to their appearance, while men do not heed it. In addition women are more sensitive to emotion and empathy while men are more likely to care about better physical environment and quicker and more flexible response than women [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the consumption of sugary foods in this age group that increases while tooth brushing and dental visits are not of serious concern. 15 In addition, Jabodetabek, shows that the mean DMF-T is high in the age group of 12 years old. The high average value of DMF-T can be due to the presence of hormonal fluctuations during puberty that results in salivary biochemical composition and reduced salivary flow rate causing the cavity to be more cariogenic in the 12-year age group.…”
Section: Discussionmentioning
confidence: 97%